Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) Untuk Meningkatkan Aktivitas Dan Hasil Belajar Akidah Akhlak Pada Materi Mengenal Allah Melalui Asmaul Husna Siswa Kelas V MIN 1 Kota Lhoksemawe - Yusrawati, Yusrawati (Jurnal Cakrawala, 2024)
The purpose of this study is to improve the activities and learning outcomes of Akidah Akhlak students of class V MIN 1 Lhoksemawe City on the material of knowing God through Asmaul Husna lesson 2017/2018. The number of students is 31 students with 14 male students and 17 female students. This class action research was conducted in the 2017/2018 school year. This class action research was carried out within a period of 3 months, from August 2017 to October 2017 in odd semesters. The research procedure consists of pre-research, one-cycle planning, one-cycle action execution, one-cycle observation, one-cycle reflection, two-cycle planning, two-cycle action execution, two-cycle observation and second-cycle reflection. The data collection technique is to collect test scores that are carried out at the end of each learning in each cycle using a question instrument (written test). Observation data is carried out by looking at student activity in the learning process. The data are analyzed by means of percentage statistics. The results showed that there was an increase in the completeness of student learning outcomes from 41.93% in the pre-study increased to 67.74% in cycle I and increased to 83.87% in cycle II. Student learning activities have increased from the enough to good category and the good category increased to excellent. The application of the contextual teaching and learning (CTL) model can improve the activities and learning outcomes of Akidah Akhlak students of class V MIN 1 Lhoksemawe City on the material of knowing God through Asmaul Husna lesson 2017/2018.